Contestation of Meanings in Mocera Tasi Ritual of the Wotu Community in East Luwu - Mustafa, Zulhasari (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2020)
This research aims to answer the problems of meaning, theological values, philosophical values, and discursive practices in the context of the ritual mocera tasi with qualitative research methods. This research uses the cultural studies approach. Locus of the research included Lampenai Village and Bawalipu Village, Wotu District, East Luwu Regency. Primary data were collected by observations, interviews, and written documents from ritual practitioners. Primary data were collected by literature sources related to research. Resource persons were research informants. Informants were selected using a purposive sampling technique. Data were processed by identification, categorization, and classification stages. Data were analyzed by reduction, display, interpretation, inference, and verification process. The results showed that knowledge was gained by the contestation of meanings around the mocera tasi ritual. Mocera tasi as a spirit of the life of ethnic Wotu people has meaning based on theological and philosophical values. Theological values educate the Wotu community to give thanks to the Creator and give alms for all the blessings that were obtained. Philosophical values teach the emotional soul between humans and nature and fellow creatures created by Allah. The study implied that offending the mocera tasi ritual means touching on the knowledge and beliefs of the ritual participants. Therefore, changing or stereotyping of the mocera tasi ritual will touch on the aspects of the knowledge and beliefs of the Wotu ethnic community. يهدف هذا البحث إلى الإجابة على مشاكل المعنى والقيم اللاهوتية والقيم الفلسفية والممارسات الاستطرادية في سياق موﭼيرا تاسى مع أساليب البحث النوعي. واستخدم البحث منهج الدراسات الثقافية. تضمن محور البحث قرية لامبيناي وقرية باواليبو، منطقة ووتو، منطقة لوو الشرقية. وتم جمع البيانات الأولية عن طريق الملاحظات والمقابلات والوثائق المكتوبة من ممارسي الطقوس. تم جمع البيانات الأولية من خلال مصادر الأدب المتعلقة بالبحث. كان الأشخاص المرجعيون مخبرين للبحوث. وتم اختيار المخبرين بإستخدام تقنية أخذ العينات هادفة. تمت معالجة البيانات عن طريق مراحل التحديد والتصنيف والتصنيف. تم تحليل البيانات عن طريق الاختزال والعرض والتفسير والاستدلال وعملية التحقق. أظهرت النتائج أن المعرفة اكتسبت من خلال الطعن في المعاني حول طقوس موﭼيرا تاسى كروح لحياة شعب ووتو العرقي له معنى قائم على القيم اللاهوتية والفلسفية. القيم اللاهوتية تثقف مجتمع ووتو لتقديم الشكر للخالق وإعطاء الصدقات لجميع النعم التي تم الحصول عليها. القيم الفلسفية تعلم الروح العاطفية بين البشر والطبيعة والمخلوقات التي خلقها الله. أشارت الدراسة إلى أن الإساءة إلى طقوس موكيرا تاسي تعني لمس معارف ومعتقدات المشاركين في الطقوس. لذلك، فإن تغيير أو تنميط طقوس الموزيرا سوف يتطرق إلى جوانب المعرفة والمعتقدات الخاصة بمجتمع ووتو العرقيPenelitian ini bertujuan untuk menjawab masalah makna, nilai-nilai teologis, filosofis, dan praktik diskursif dalam konteks ritual mocera tasi dengan metode penelitian kualitatif. Penelitian ini menggunakan pendekatan studi budaya. Lokasi penelitian meliputi Desa Lampenai dan Desa Bawalipu, Kecamatan Wotu, Kabupaten Luwu Timur. Data primer dikumpulkan dengan observasi, wawancara, dan dokumen tertulis dari praktisi ritual. Data primer dikumpulkan oleh sumber literatur yang terkait dengan penelitian. Narasumber adalah informan penelitian. Informan dipilih menggunakan teknik purposive sampling. Data diproses oleh tahap identifikasi, kategorisasi, dan klasifikasi. Data dianalisis dengan reduksi, tampilan, interpretasi, inferensi, dan proses verifikasi. Hasil penelitian menunjukkan bahwa pengetahuan diperoleh dengan kontestasi makna di sekitar ritual mocera tasi. Mocera tasi sebagai ruh kehidupan etnis Wotu memiliki makna berdasarkan nilai-nilai teologis dan filosofis. Nilai-nilai teologis mendidik komunitas Wotu untuk bersyukur kepada Sang Pencipta dan memberikan sedekah untuk semua berkat yang diperoleh. Nilai-nilai filosofis mengajarkan jiwa emosional antara manusia dan alam dan sesama makhluk yang diciptakan oleh Allah. Studi ini menyiratkan bahwa menyinggung ritual mocera tasi berarti menyentuh pengetahuan dan kepercayaan para peserta ritual. Karena itu, perubahan atau stereotip ritual mocera tasi akan menyentuh aspek pengetahuan dan kepercayaan komunitas etnis Wotu.